(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Medical secretaries play a crucial role in the efficient functioning of healthcare facilities by managing administrative tasks and facilitating communication between patients and healthcare providers. Mastery of medical terminology is essential for medical secretaries to accurately transcribe medical documents, schedule appointments, and interact effectively with patients and other healthcare professionals. This abstract provides an overview of medical terminology essentials for medical secretaries, covering key components such as root words, prefixes, suffixes, and combining forms. Common medical terms related to anatomy and physiology, body systems, diagnostic procedures and tests, as well as common conditions and diseases are discussed. The importance of medical terminology proficiency for accurate documentation, effective communication, patient safety, and efficient workflow in healthcare settings is emphasized. Resources for learning medical terminology, including textbooks, online courses, medical dictionaries, and interactive learning tools, are also highlighted. By acquiring proficiency in medical terminology, medical secretaries can enhance their contribution to the healthcare team and ensure the delivery of high-quality patient care.